2015
DOI: 10.21863/johar/2015.10.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of Employees Job Satisfaction and the Role of Male and Female Differences: An Empirical Study at Hotel Industry in Iran

Abstract: Employee satisfaction is a parameter used to measure of the extent to which employees are pleased with their particular jobs and working environment. Continuously improving the spirits and self-confidence among employees can be of incredible benefits to any organization, given that happy employees are anticipated to put in more energy and time, take less leave of absence, and remain dedicated to the company. There are a number of factors that improve or sustain high employee satisfaction, which sensible employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, observations differ and there is hardly any unanimity in the current literature with regards to relationships between demographic variables and other dependant variables such as, job satisfaction and job stress. While, in their study in five-star hotels, Kara et al (2012) have found significant gender differences in job satisfaction of employees, Hashemi et al (2015) found no significant difference between gender of hotel employees in Iran and their job satisfaction.…”
Section: Review Of Literature Demographic Factors and Job Satisfactionmentioning
confidence: 84%
“…However, observations differ and there is hardly any unanimity in the current literature with regards to relationships between demographic variables and other dependant variables such as, job satisfaction and job stress. While, in their study in five-star hotels, Kara et al (2012) have found significant gender differences in job satisfaction of employees, Hashemi et al (2015) found no significant difference between gender of hotel employees in Iran and their job satisfaction.…”
Section: Review Of Literature Demographic Factors and Job Satisfactionmentioning
confidence: 84%
“…Previous research on gender differences in relation to attitudes and behaviors within the hospitality industry has produced mixed findings. For example, a study of Iranian hotels found employees were moderately satisfied with their job, with no significant difference between male and female employees’ job satisfaction (Hashemi, Kiumarsi, Jusoh, & Hashemi, 2015). In opposition, a different study excluded the influences of variables such as age, marital status, income level, educational backgrounds, job tenure, and length of employment and found that staff job satisfaction levels were significant different between genders (Kara, Uysal, & Magnini, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is not easy to get the highest satisfaction value on the recognition item because it is at the fourth level, which the individual will only obtain if he or she has passed the previous levels of satisfaction, namely psychological, security, and social. 21,26 In this study, the reason the recognition variable is included in the important variables is that currently, not many people have noticed the presence of pharmacists, which may be due to pharmacists not having enough time to provide counseling or other interactions. In addition, pharmacists have other responsibilities as drug supply managers with monthly reporting to the Health Office and the Food and Drug Administration, which can reduce interaction time with patients.…”
Section: Extrinsic Factormentioning
confidence: 99%